Neuro Linguistic Programming in Empowerment Staff - Sevim Şen; Esra Uğur (Association of Nurse Managers, 2019)
Empowerment refers to giving power to employees. Empowerment is basically to improve the employee's expertise, to ensure that they see opportunities, to encourage them to make the necessary decisions, and to change their attitude towards work. Neuro-Linguistic Programming (NLP) is a field of study that studies the processes of thinking, language and behavior and how to use these processes effectively to achieve their goals. With NLP, it is possible to speed up the learning process, to strengthen communication, to increase sensitivity, to reach flexibility by increasing choices, to increase cooperation, to direct emotions and thoughts, and to mobilize consciousness to determine strength and resources. The purpose of this compilation is; The importance of staff empowerment and the sharing of recommendations on the use of NLP techniques for empowerment. It is thought that it will contribute to the implementation of NLP principles and techniques in strengthening health workers and managers.